2020
DOI: 10.1016/j.heliyon.2020.e05119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cellular safety and the chemical composition of the peanut (Arachis hypogaea L.) ethanolic extracts

Abstract: Arachis hypogaea L. (Leguminosae) is distributed in tropical and subtropical areas. Peanut has high nutritional and commercial value. Scientific research showed that peanut has biological properties such as anticancer, antioxidant, antiinflammatory. However, it is necessary to know if consumption of peanut, either as food or as a phytopharmaceutical implies a health risk. The aim was to evaluate cytotoxicity and genotoxicity of ethanolic extracts from A. hypogaea . Also, chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Jack bean, peanut, and winged bean are vegetable legume crops that grow a lot in tropical areas (Alalade et al 2016;Akande 2016;Candela et al 2020). These plants are widely used by people because they are rich in vitamins, proteins, and minerals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jack bean, peanut, and winged bean are vegetable legume crops that grow a lot in tropical areas (Alalade et al 2016;Akande 2016;Candela et al 2020). These plants are widely used by people because they are rich in vitamins, proteins, and minerals.…”
Section: Discussionmentioning
confidence: 99%
“…According to Akande (2016), jack bean is reported to contain antinutritional substances, namely cyanogenic glycosides, trypsin inhibitors, concanavalin, canavanine, canaline, phenols, and saponins. Peanuts have substances of secondary metabolites, such as linoleic acid, oleic acid, and palmitic acid, also anti-nutritional substances, such as tannins, cardiac glycosides, and nitrates (Candela et al 2020), whereas winged beans conceive tannin, oxalate, and phytate as anti-nutritional compounds (Alalade et al 2016). Not much information is reported that these three plants cause severe poisoning in livestock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was determined that the average lignoceric acid ratio for two years varied between 1.07% and 1.78% (Table 6). The amount of lignoceric acid varied between 1.01-1.88%; Konuskan et al (2019), ligneceric 1.62%; Candela et al (2020) reported that the rate of lignoceric acid varies between 1.0-1.86%. The ratio of behenic acid in the studies was similar to our study.…”
Section: Black Sea Journal Of Agriculturementioning
confidence: 99%
“…In addition, it is also ingested in the form of flour and candy (Limmongkon et al, 2018;Treuter et al, 2017). It is a legume with an abundance of nutrients and chemical constituents, such as proteins, carbohydrates, fibers, fats, niacin, folate, thiamine, arachidic acid, flavonoids, magnesium, phosphorus, polyphenols, and bioactive components (Limmongkon et al, 2018;Menis Candela et al, 2020).…”
Section: Arachis Hypogaeamentioning
confidence: 99%